2016
DOI: 10.1038/ajgsup.2016.17
|View full text |Cite
|
Sign up to set email alerts
|

Using Markers in IBD to Predict Disease and Treatment Outcomes: Rationale and a Review of Current Status

Abstract: Biomarkers, radiology fi ndings, and endoscopic studies, together with clinical assessment of patients with infl ammatory bowel disease, can be used to help determine prognosis, assess disease activity, and increasingly to inform treatment decision-making. This article reviews the current "state of the science" regarding the multitude of different tests that can be performed and how these can be used in the clinic to guide management. Initially, when patients present with symptoms suggestive of infl ammatory b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 84 publications
(85 reference statements)
0
9
0
Order By: Relevance
“…In humans, use of non-invasive tests enables monitoring disease relapse. 36,37 The selected serological markers are IgA based because they have a short half-life (3-6 days). 38 When conducting serial measurements in enrolled dogs undergoing treatments, our study showed encouraging results, albeit in a limited subcohort, supporting the use of single-assay read outs as a noninvasive tool to monitor disease progression and response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, use of non-invasive tests enables monitoring disease relapse. 36,37 The selected serological markers are IgA based because they have a short half-life (3-6 days). 38 When conducting serial measurements in enrolled dogs undergoing treatments, our study showed encouraging results, albeit in a limited subcohort, supporting the use of single-assay read outs as a noninvasive tool to monitor disease progression and response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Routine blood tests (e.g., C-reactive protein (CRP), erythrocyte sedimentation rate (ESR)) are performed to evaluate disease activity [42, 43].…”
Section: Methodsmentioning
confidence: 99%
“…IBD is divided into two major types, including ulcerative colitis and Crohn’s disease and have been characterized by chronic and recurring intestinal inflammation. (Lichtenstein and McGovern, 2016). The most symptoms of IBD are known to diarrhea, fatigue (Singh et al, 2011), palindrimic inflammation and injury of epithelial tissue (de Moreno de LeBlanc et al, 2015), which leads to reduce of life quality (Simren et al., 2002).…”
Section: Introductionmentioning
confidence: 99%